2020
DOI: 10.1002/qre.2582
|View full text |Cite
|
Sign up to set email alerts
|

Statistical inference for constant‐stress accelerated life tests with dependent competing risks from Marshall‐Olkin bivariate exponential distribution

Abstract: This paper considers a constant‐stress accelerated dependent competing risks model under Type‐II censoring. The dependent structure between competing risks is modeled by a Marshall‐Olkin bivariate exponential distribution, and the accelerated model is described by the power rule model. The point and interval estimation of the model parameters and the reliability function under the normal usage condition at mission time are obtained by using the maximum likelihood estimation method and the bootstrap sampling te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In such case, the system fails if any one component fails, it is indeed an example of dependent competing risk set up. In the literature, we find the study on dependent competing risk in Bai et al [2], Cai et al [13], Feizjavdian and Hashemi [23], Kundu [26], Kundu and Mondal [25], Shen and Xu [34], Lyu et al [29] and references therein.…”
Section: Dutta and Kayalmentioning
confidence: 96%
See 1 more Smart Citation
“…In such case, the system fails if any one component fails, it is indeed an example of dependent competing risk set up. In the literature, we find the study on dependent competing risk in Bai et al [2], Cai et al [13], Feizjavdian and Hashemi [23], Kundu [26], Kundu and Mondal [25], Shen and Xu [34], Lyu et al [29] and references therein.…”
Section: Dutta and Kayalmentioning
confidence: 96%
“…The Bias of MLEs and DPDEs are given in the Table (2) for the pure data and contaminated data scheme. It is observed that MLEs are highly affected by contamination as biases of MLEs are increased in contaminated data setting compared to pure data setting.…”
mentioning
confidence: 99%
“…The exponential distribution and its generalizations play an important role in many areas of science, including physics, chemistry, medical sciences and reliability engineering (see e.g. [1,2,16,19]). Dombi et al [6] introduced the epsilon distribution, which may be treated as an alternative to the exponential distribution.…”
Section: Introductionmentioning
confidence: 99%